Cytokine production in lungs and adrenal glands of high and low antibody producing mice infected with Paracoccidioides brasiliensis - Pinto, J. G. G.; Martins, L. A.; Cavalheiro, J. S.; Acorsi, M. J.; Pedrini, S. C. B.; Soares, A. M. V. C.; Oliveira, S. L. (Taylor & Francis Ltd, 2006)
Mice genetically selected for high (H) and low (L) antibody production (HIV-A and L-IV-A) were used in an experimental model of paracoccidioidomycosis. In a previous work, it was observed that male HIV-A animals were more susceptible to the infection due to adrenal gland damage. Male HIV-A and LIV-A animals were intravenously inoculated with Paracoccidioides brasiliensis (strain 18) and sacrificed 2, 4, 6, 8 and 10 weeks after inoculation. At each time interval, lungs and adrenals were removed to estimate recoverability of the fungus, as well as to determine Th1 (IFN-gamma, TNF-alpha) and Th2 (IL-4 and IL-10) cytokine profiles. While viable fungi recoverability from the lungs of HIV-A mice was higher after 4 and 8 weeks, there was less fungal recovery from the adrenals of LIV-A animals after the 2nd week, with total fungal elimination after the 8th week. With regard to Th2 cytokines, there was an inhibition in IL-4 production in the organs from infected animals, the extent of which varied according to the organ and the time period after initiation of infection. IL-10 production was found to be lower in both organs. Determination of Th1 cytokines revealed that IFN-gamma production increased in both organs, mainly in the adrenal of LIV-A after 8 and 10 weeks, when these animals showed a total fungal elimination. A significant difference was observed between HIV-A and LIV-A concerning TNF-alpha production in both organs and at all recovery times, in that LIV-A produced a higher level of this cytokine, mainly in the adrenal. These results may explain the high susceptibility of HIV-A to P. brasiliensis infection, is due, at least in part, to adrenal involvement. The higher production of Th1 cytokines by LIV-A in comparison to HIV-A mice may account for LIV-A resistance to P. brasiliensis infection. Our data reveal the importance of this experimental model in the study of the adrenal involvement in paracoccidioidomycosis, since this gland may be highly compromised in the patients, leading to the development of Addison's Disease.
Keywords: Biozzi mice; experimental paracoccidioidomycosis; cytokines; adrenal gland